Learning motivation, school, anxiety and well-being in middle childhood - Pileckaitė-Markovienė, Margarita (Psichologija, 2001)
This article deals with problem of learning motivation, school anxiety and well-being in middle childhood. The aim of investigation was to analyse inner consistency of Learning Motivation Scale, structure of learning motivation of primary school children and it's interrelations with school anxiety and well-being. Learning Motivation Scale (Zambacevičienė, Janulytė, 1998), Semantic Differential Type Scale for well-being in school (Beres-nevičienė, 1995) and Test Anxiety Scale for children (Sarason, Feld, Levis, 1960, by Augis, 1984) were used as evaluational tools. 681 children from third and forth grade (355 girls, 326 boys) were investigated by these methods.The results showed the strong inner consistency of Learning Motivation Scale (Cronbach alpha 0,79). Rest-retest showed rather strong internal reliability of the scale (r = 0,71). Got data showed that structure of learning motivation of primary school children consisted from motives of social recognition, negative stimulation and inner motive. It was found that learning motivation had positive connection with well-being in school by parameters "likable", "pleasant", "interesting", "useful". Learning motivation was positively connected with school anxiety as well. School anxiety of primary school children had negative correlation with their well-being by the parameters "easy to learn" and "going well to learn".
Keywords: learning motivation; school; anxiety; well-being; middle childhood